Características e desfechos gestacionais relacionados ao diabetes mellitus gestacional segundo diferentes critérios diagnósticos: um estudo de coorte - Souza, Cláudia Meurer (2020)
Introduction: Gestational diabetes has an impact on maternal and child health, however there is no consensus about the diagnostic criterion. Objective: to evaluate the clinical characteristics and gestational outcomes in normoglycemic pregnant women and pregnant women diagnosed with gestational diabetes mellitus, according to diagnostic criterion. Methods: prospective cohort study. Pregnant women from the third trimester on participated, with the occurrence of GDM being verified, according to different diagnostic criteria. The risk factors for GDM and the outcomes of the disease in pregnancy, delivery, and child were evaluated by multivariate logistic regression, expressed by the Odds Ratio (OR) and 95% confidence interval (CI). Results: 8.7% of women were diagnosed with GDM (glycemia ≥95) and another 8% would have glycemic levels ≥92mg/dL for diagnosis by the most recent criterion. Pre-gestational obesity (OR 6.04 95%CI 1.28-28.41), previous diseases (OR 6.38 95%CI 1.24-32.09) and excessive weight gain (OR 8.67 95%CI 1.8-41.9) were factors related to GDM, plus age ≥30 years (OR 2.69 95%CI 0.57-12.81) and low nutritional knowledge (OR 5.03 95%CI 1.26-20.18). Regardless of the diagnostic criterion, women with GDM had a higher risk of having intercurrences in pregnancy and intercurrences with the newborn. Glycemia ≥92mg/dL was a factor related to intercurrence in delivery (OR 4,95 95% IC1.79-13.68), cesarean section (OR 6.43 95%IC 2.05-20.13), large newborn for gestational age (OR 7.64 95%IC 2.83-10.58), low 5th minute Apgar (OR 16.04 95%IC 3.76-68.43) and neonatal asphyxia (OR 11.46 95%IC 3.55-37.07). Conclusion: The adoption of the glycemic cutoffs ≥ 92mg/dL pointed to an important portion of the population without diagnosis, suggesting that this cutoff point, more sensitive, should be used in order to guide women timely and minimize undesirable outcomes in pregnancy, especially in neonates.